2020
DOI: 10.1016/j.kint.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

International consensus definitions of clinical trial outcomes for kidney failure: 2020

Abstract: Kidney failure is an important outcome for patients, clinicians, researchers, healthcare systems, payers, and regulators. However, no harmonized international consensus definitions of kidney failure and key surrogates of progression to kidney failure exist specifically for clinical trials. The International Society of Nephrology convened an international multistakeholder meeting to develop consensus on this topic. A core group, experienced in design, conduct, and outcome adjudication of clinical trials, develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 36 publications
(46 reference statements)
5
74
0
13
Order By: Relevance
“…Based on recent literature, an international consensus on definitions of endpoints for clinical trials of kidney failure has emerged, coming to the conclusion that the preferred threshold for kidney function loss is a sustained ≥40% decline in eGFR from baseline. 3 This threshold of kidney function loss is clinically meaningful, predictive of future need for kidney replacement therapy, and can be captured within the relatively brief timeframe of outcome trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on recent literature, an international consensus on definitions of endpoints for clinical trials of kidney failure has emerged, coming to the conclusion that the preferred threshold for kidney function loss is a sustained ≥40% decline in eGFR from baseline. 3 This threshold of kidney function loss is clinically meaningful, predictive of future need for kidney replacement therapy, and can be captured within the relatively brief timeframe of outcome trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta‐analyses of kidney outcomes from SGLT2 inhibitor trials have not, however, used uniform definitions of “significant kidney function decline”, which have differed between the trials 1 . The importance of using consistent definitions of eGFR decline has been emphasized by recent expert consensus statements, as thresholds for kidney function loss must be clinically relevant and also feasible over the 2–4 year time frame of clinical outcome trials 3,4 . Accordingly, our aim was to examine kidney composite outcome data from four SGLT2 inhibitor CVOTs using a uniform sustained ≥40% eGFR decline definition 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD described in the eligible studies must have been identified by a physician and the diagnosis must have been made based on the criteria from the Improving Global Outcomes (KDIGO) Consensus Conference which defines CKD as kidney damage (albumin-to-creatinine ratio > 30 mg/g in two of three spot urine specimens) or glomerular filtration rate (GFR) < 60 mL/min/1.73m 2 for 3 months or more, irrespective of the cause [ 19 21 ]. Silent myocardial ischemia (SMI) must have been diagnosed by a physician and diagnosed in patients who display no symptoms during an exercise or pharmaceutical stress test but who exhibit transient ST-segment changes, perfusion defects, or reversible regional wall motion abnormalities [ 22 ], or patients who display no symptoms and a myocardial ischemia is later diagnosed based on myocardial imaging evidence or pathological findings on autopsy [ 23 , 24 ].…”
Section: -Methodsmentioning
confidence: 99%
“…The consensus definition has recently been published with subsequent audit of its use planned. 3 Future goals of ISN-ACT Maximum benefit of any intervention requires it to be generalizable, which requires testing in diverse populations around the world. Few trials are undertaken in low-and middle-income countries, despite this being where most of the world's population lives.…”
Section: International Consensus Definitions Of Clinical Trial Outcomes For Kidney Failurementioning
confidence: 99%